Impact of Disaster on Economic Performance of ASEAN-9: Does Philanthropy Help? - Azhar, Thifal; Majid, M. Shabri Abd.; Sartiyah, Sartiyah; Dawood, Taufiq C (Jurnal Ekonomi & Studi Pembangunan, 2022)
This study aims to determine the moderating role of religious philanthropy in reducing the impacts of disasters to economic problems, namely inequality, poverty, and economic growth of ASEAN-9 over the period from 2000 to 2020. By using a panel moderated regression analysis, the study found that disasters significantly contributed to higher levels of economic growth, income disparity, and poverty. In addition, philanthropy is found to have a negative moderating role in the effects of disasters on economic growth, inequality, and poverty. The findings showed an effective role of philanthropy in reducing the impacts of disasters on economic growth, income disparity, and poverty in ASEAN-9. Our findings provide an important benchmark for the formulation of government policies to mitigate disaster risks on economic problems through the enhancement of religious philanthropic institutions.